THE MODERATING ROLE OF GOOD CORPORATE GOVERNANCE IN THE RELATIONSHIP BETWEEN ENVIRONMENTAL DISCLOSURE AND GREEN INNOVATION AND FIRM VALUE - Kampono Imam Yulianto; Zara Tania Rahmadi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The purpose of this research is to analyze the effect of enviromental disclosure and green innovation on firm value moderated by GCG. This research uses data analysis with a correlation and panel data regression approach assisted by Eviews 12 software. The data used is secondary data in the form of financial statements companies obtained from the official website of the Indonesia Stock Exchange for the years 2020-2024, with a total of 20 companies and 100 observations. the results show that when combined, environmental disclosure, green innovation, and GCG have a significant impact on firm value. However, when looked at individually, only environmental disclosure and GCG have a significant positive effect on firm value. Green innovation on its own does not have a significant influence. When tested as a moderating variable, GCG was able to strengthen the relationship between green innovation and firm value. However, GCG did not strengthen the relationship between environmental disclosure and firm value. This research is expected to be a consideration for investors so that companies can implement good corporate governance through green innovation and environmental disclosure as a form of concern for the environment and sustainability.